Sports effect on depression level of elementary school students - Ahmet Gursel Oguz; Oksay Oguz (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to analyze sports and exercises effects on depression levels of elementary school students. The research group formed a total of 203 students, including 104 students who exercise (amateur athletes, playing in school teams, etc.)  The Depression Scale for Children (CDS) and Beck Depression Scale was used as a data collection tool in the study. The applicability of parametric or nonparametric tests was examined by comparing the normal distribution of values and variance equality when analyzing data to measure depression level of subjects. The normal distribution fitness test for the data was tested using the Kolmogorov-Smirnov test, again using the Levene’ test for variance homogeneity. In order to apply the parametric tests, both normal distribution suitability and variance homogeneity are required. Non-normal distribution of data or homogeneous variance requires using nonparametric tests. One-way ANOVA test for more than two group of parametric tests and two independent T-tests for two independent groups were used for the analysis of the data as a result of Kolmogorov-Smirnov test and Levene’ test. The difference between the two independent sample T-test results for determining whether the depression scores of the performing and non-performing individuals are different is P = 0.039 lt;0,05.According to this, doing sports affects the score of depression. Individuals doing sports were found to be lower than students who did not score depression. There was no significant difference in the number of other siblings, age, educational status, maternal profession, father's occupation, mother education, father education, income and sex variables, depression scores were compared at 0.05 level. As a result, it was found that sports and exercise were important in reducing the adverse effects of depression or entering primary school children. In addition, emphasis should be placed on the preparation of adolescents for the direction of children's spores.